ENGLISH DIGITAL TALKING BOOKS AS MEDIA TO TEACH NARRATIVE WRITING (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2016)
There are many studies have been conducted to investigate the use of talking book, but not with the digital talking book. In other words, the use of digital talking book has not been widely prevalent among the EFL learners. This study investigated whether there is any significant differences on the students’ writing achievement between those who are taught by using English digital talking books and those who are taught by using simple brochure as media. The population of the study was the twelfth grade students of SMA N 1 Comal, Pemalang, in the academic year of 2014/2015). There were 80 students, divided into two groups of 40, participated in this quasi experimental study as experimental and control group. The result of t-test showed that the difference between the students who were taught using English digital talking books and those who were taught using simple brochures can’t be seen significantly. It also showed that in this study, English digital talking books were more effective than simple brochures to improve students’ ability in writing a narrative text.